Study on the Challenges of Big Data Computing and the Security Issues Associated with Big Data in Hadoop: Exploring the Solutions for Big Data Challenges and Security Issues in Hadoop (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As the world is digitizing the speed at which the quantity of records exceeds due to exclusive assets in specific format, it is not always feasible for the conventional machine to calculate and analyze this kind of massive facts for which massive recording tool like Hadoop is used, which is an open supply software. In a dispensed environment, it shops and computes records. Big Data Systems have become increasingly critical in the past few years. In reality, most organizations depend on data from massive amounts of information. Modern data methodology, however, indicates a reduced overall efficiency, reliability, incremental sensitivity, and lack of scalability. Masses of work have been done to clear up the confusing Big Data headache. As a result, different technology styles have been advanced. As the arena is being digitized the velocity in which the amount of information is overdue from different assets in different layout, it is not feasible for the traditional system to measure and analyze this type of large records for which massive data tool such as Hadoop is used, which is an open source software program.